Decision support system for dental clinic - Fadzhila, Sabri (2011)
Decision Support System for Dental Clinic is a web based application.This system is providing to implement process in the Dental Clinic starting with patient registration until dentist or nurse settled the patient treatment.The objective of this project is develop Decision Support System for Dental Clinic that provide information about the dentist and nurse profile,patient information include patient personal detail,patient treatment,patient appointment, patient billing,and dental treatment and disease.Dental treatment and disease module provide information about the cause of tooth extraction and tooth filling.It is allow the dentist or nurse to trace whether the patient needs to make tooth extraction or tooth filling.During the system development Macromedia Dreamweaver 8 is used in order to create interface and coding.The MySqI database is create using XAMPP.This system is gives advantages to the all both users clinic staff and end user especially patient,where the two users can access the system.